Landscape ecological study of the Orthopteran insects in the Southern Mezőföld - Pápai, János; Krausz, Krisztina (JOURNAL OF LANDSCAPE ECOLOGY, 2008)
The different sized and mosaic-like habitats of various surfaces of sandy and loess grasslands, marshes and marshy fields of the Southern Mezőföld offer a good opportunity to study landscape ecological analyses in respect of one particular insect group, that of the Orthoptera. The research made on 17 patches of 11 habitats differing in size and vegetation have pointed out the role of ecological parameters as well as the features of the specific habitats. This area owns a rich Orthoptera fauna: there are 39 species, wich is the 32% of the total national fauna. In the structure of the orthopteran assemblages, more has been determining the role of different degradation state of habitats rather than the total surface, homogenity and the average plant height. As far as the landscape ecological parameters are concerned, the permeability of the surrounding matrix for orthopteran insects had the greatest significance. To a smaller extent, the distance of the nearest potential colonial source, the existance of a possible corridor and the size and distance between the spots could have an influence as well. In the smaller, more isolated patches there was a greater dimension of species with good migrating skills, which can colonise better.